Synthesis and efficient use of low-cost natural red clay catalyst for the production of upgraded fuel oil using pyrolysis of waste expanded polystyrene and in situ vapour phase hydrogenation - Verma A.; Sharma S.; Pramanik H. (My University, 2025)
The waste expanded polystyrene (WEPS) was subjected to the pyrolysis and in situ hydrogenation process in a laboratory fabricated innovative reactor on a red clay catalyst in the temperature range of 400°C to 700°C. Five different catalysts were synthesized from the eco-friendly and non-toxic red clay, that is, red clay in natural form (RC), red clay calcined at 600°C (RC-600), red clay calcined at 700°C (RC-700), red clay calcined at 800°C (RC-800), and red clay calcined at 900°C (RC-900). The catalytic pyrolysis of WEPS, in situ hydrogenation, and aromatization were performed keeping the synthesized catalyst in different reactor arrangements, that is, liquid phase/X-type, vapour phase/Y-type, and multiphase/XY-type. The raw and calcined red clay catalysts were characterized by various characterization techniques such as SEM-EDX, BET, XRD, and FTIR. The calcination temperature greatly influenced the surface morphology and surface area of the red clay catalysts. The surface morphology of calcined red clay catalyst RC-800 shows nano cluster form of particles with very high porosity. The highest surface area of 29.25 m2/g and highest silica content of 56.82 wt% were found for the RC-800 catalyst. Furthermore, the XRD analysis ensured the presence of illite-micas, α-quartz, κ-kappa alumina, δ-delta alumina, and θ-theta alumina in the RC-800 catalyst only. The presence of strong Bronstedacid sites in RC-800 catalyst was confirmed by the FTIR analysis. The highest liquid yield of 94.37 wt% was obtained for the thermal pyrolysis of WEPS at the optimum temperature of 650°C and heating rate of 15°C/min. The maximum BTE content of 11.38 wt% was recorded for the pyrolysis oil obtained from the thermal pyrolysis of WEPS at the same optimum conditions. On the other side, the highest liquid yield of 88.82 wt% was obtained for the X-type pyrolysis at the optimum temperature of 600°C and heating rate of 15°C/min using red clay catalyst RC-800. The Y-type and XY-type pyrolysis produced maximum liquid yield of 80.81 wt% and 79.47 wt%, respectively, at the optimum temperature of 550°C and at heating rate of 15°C/min using the same red clay catalyst RC-800. However, the multiphase/XY-type pyrolysis produced the highest BTE content of 27.62 wt% and lowest styrene content (60.75 wt%) at a temperature of 550°C using RC-800 catalyst among all types of pyrolysis. The maximum styrene content of 84.74 wt% was found in pyrolysis oil obtained from thermal pyrolysis of WEPS at optimum conditions. The styrene content obtained reduced significantly from 68.83 wt% to 60.75 wt% when the reactor arrangement was changed from X-type to XY-type. The pyrolysis oil obtained from XY-type/multiphase pyrolysis was found suitable for the use in internal combustion (IC) engine. © 2022 John Wiley & Sons Ltd.